Curcumin induced oxidative stress attenuation by N-acetylcysteine co-treatment: a fibroblast and epithelial cell in-vitro study in idiopathic pulmonary fibrosis - L. R. Rodriguez; S. N. Bui; R. T. Beuschel; E. Ellis; E. M. Liberti; M. K. Chhina; B. Cannon; M. Lemma; S. D. Nathan; G. M. Grant (BMC, 2019)
Abstract Background Idiopathic Pulmonary Fibrosis (IPF) is a fatal lung disease of unknown etiology with only two federally approved drug options. Given the complex molecular pathogenesis of IPF involving multiple cell types and multiple pathways, we explore the effects of a potential antifibrotic and antioxidant drug combination. Curcumin is a polyphenolic compound derived from turmeric with significant biological activity including a potential antifibrotic capacity. N-acetylcysteine (NAC) is a precursor to the antioxidant glutathione. To advance our understanding of these molecules, and to identify a clinical application, we present a small number of focused experiments that interrogates the effect of curcumin and NAC on pathways relevant to IPF in both fibroblasts and epithelial cells. Methods Primary epithelial cell and fibroblasts isolated from patients with IPF were challenged with a combination treatment of NAC and curcumin. Evaluation of the antifibrotic potential and effect on oxidative stress was performed through QPCR gene expression analysis and functional assays including scratch tests, viability assays, and measurement of induced reactive oxygen species. Results We demonstrate that curcumin alone does have antifibrotic potential, but that effect is accompanied by proapoptotic increases in oxidative stress. Coupled with this, we find that NAC alone can reduce oxidative stress, but that epithelial cell viability is decreased through this treatment. However, co-administration of these two molecules decreases oxidative stress and maintains high cell viability in both cell types. In addition, this co-treatment maintains an antifibrotic potential. Conclusions These findings suggest a novel application for these molecules in IPF and encourage further exploration of this potential therapeutic approach.